Finding Political Identities Young People in a Changing Europe - Ross, Alistair (Palgrave Politics of Identity and Citizenship Series,, 2019)
This book explores how young people in Europe construct their political identities. Based on small discussion groups with 2000 young people across 29 European states, Alistair Ross explores how 13 to 20 year olds build identities in contemporary society, creating contingent narratives of local, national and European identities with families, friends and social media. As well as exploring what these kaleidoscopic identities look like and the sources they draw on, it also examined how these accounts are assembled and integrated with each other. The study uses deliberative discussions to allow young people to develop their own constructs and terms in conversation with each other. This analysis presents a complex polyphonic of political beliefs and values of rights, which young Europeans attach to political structures and institutions that often transcend traditional boundaries of state and nation. Finding PoliticalIdentities will be of interest to postgraduate students and academics across Education, Sociology, Politics and European Studies, especially those with a focus on Social Constructionism, Citizenship, Identity Studies, Social Policy, and Youth Studies. .